Homology-based inference sets the bar high for protein function prediction - Tobias Hamp; Rebecca Kaßner; Stefan Seemayer; Esmeralda Vicedo; Christian Schaefer; Dominik Achten; Florian Auer; Ariane C. Boehm; Tatjana Braun; Maximilian Hecht; B. Mark Heron; Peter Hönigschmid; et al. (2013)
Any method that de novo predicts protein function should do better than random. More challenging, it also ought to outperform simple homology-based inference.Here, we describe a few methods that predict protein function exclusively through homology. Together, they set the bar or lower limit for future improvements.During the development of these methods, we faced two surprises. Firstly, our most successful implementation for the baseline ranked very high at CAFA1. In fact, our best combination of homology-based methods fared only slightly worse than the top-of-the-line prediction method from the Jones group. Secondly, although the concept of homology-based inference is simple, this work revealed that the precise details of the implementation are crucial: not only did the methods span from top to bottom performers at CAFA, but also the reasons for these differences were unexpected. In this work, we also propose a new rigorous measure to compare predicted and experimental annotations. It puts more emphasis on the details of protein function than the other measures employed by CAFA and may best reflect the expectations of users. Clearly, the definition of proper goals remains one major objective for CAFA.